Design of an Electrochemical Genosensor for BDNF Gene Polymorphism Sequence Detection Using an Enzymatically Labeled DNA Probe - Renato Caldevilla; Stephanie Morais; Serafim Carvalho; Rui Medeiros; Cristina Delerue-Matos; Agostinho Cruz; Marlene Santos; Maria Fátima Barroso (Engineering Proceedings, 2023)
The BDNF gene is associated with high degrees of variability in antidepressant treatments. The Val66Met polymorphism is widely known as a source of this variability, warranting growing interest in genotyping patients that undergo antidepressant treatment to better suit their needs. This paper reports on an electrochemical genosensing platform, based on gold electrodes, capable of detecting this polymorphism, through the use of synthetic enzymatically labeled DNA probes for two different BDNF alleles. The sensor showed promising results, and its applicability to real samples is currently being tested.